Discharge against Medical Advice in Surgical Patients with Posttraumatic Stress Disorder: A Case Report Series Illustrating Unique Challenges. (21st June 2017) - Brzezinski, Marek; Gregersen, Maren; Schuch, Luiz Gustavo; Sawatzki, Ricarda; Chen, Joy W.; Gauger, Grant; Kukreja, Jasleen; Cason, Brian
Abstract : Discharge against medical advice (DAMA) can have detrimental effects on patient outcomes. Recently, the diagnosis of posttraumatic stress disorder (PTSD) has been linked with DAMA in the mental health setting. However, PTSD as a risk factor for DAMA in surgical patients has not received much consideration, although such patients may be at risk for triggering or amplification of PTSD symptoms perioperatively. We present the first case report series of three surgical patients with PTSD who left the hospital AMA. These cases differ markedly from DAMA in non-PTSD patients. In all three subjects, the stress of feeling misunderstood by clinicians and the distress of public detainment by hospital security in the setting of chronic PTSD led to aggressive and risky behavior. All three subjects represented a risk to themselves and to others at the time of DAMA. Finally, all three subjects were difficult to contact for follow-up or medical care and missed appointments.